How is the Ischemic Results on Myocardial Perfusion Scintigraphy Influence the Echocardiographic Parameters (Annals of Medical Research, 2021)
None
Keywords: CAD, Myocard Perfusion Scintigraphy, Echocardiography, End Diastolic Left Ventricular Diameter